Antagonizing Retinoic Acid-Related-Orphan Receptor Gamma Activity Blocks the T Helper 17/Interleukin-17 Pathway Leading to Attenuated Pro-inflammatory Human Keratinocyte and Skin Responses - Ecoeur, Florence; Weiss, Jessica; Kaupmann, Klemens; Hintermann, Samuel; Orain, David; Guntermann, Christine (Frontiers in Immunology, 2019)
The nuclear hormone receptor retinoic acid receptor-related-orphan-receptor-gamma t (RORγt) is the key transcription factor required for Th17 cell differentiation and for production of IL-17 family cytokines by innate and adaptive immune cells. Dysregulated Th17 immune responses have been associated with the pathogenesis of several inflammatory and autoimmune diseases such as psoriasis, psoriatic arthritis, and ankylosing spondylitis. In this article, we describe the in vitro pharmacology of a potent and selective low molecular weight RORγt inhibitor identified after a structure-based hit-to-lead optimization effort. The compound interfered with co-activator binding to the RORγt ligand binding domain and impaired the transcriptional activity of RORγt as evidenced by blocked IL-17A secretion and RORE-mediated transactivation of a luciferase reporter gene. The inhibitor effectively reduced IL-17A production by human naive and memory T-cells and attenuated transcription of pro-inflammatory Th17 signature genes, such as IL17F, IL22, IL26, IL23R, and CCR6. The compound selectively suppressed the Th17/IL-17 pathway and did not interfere with polarization of other T helper cell lineages. Furthermore, the inhibitor was selective for RORγt and did not modify the transcriptional activity of the closely related family members RORα and RORβ. Using human keratinocytes cultured with supernatants from compound treated Th17 cells we showed that pharmacological inhibition of RORγt translated to suppressed IL-17-regulated gene expression in keratinocyte cell cultures. Furthermore, in ex vivo immersion skin cultures our RORγt inhibitor suppressed IL-17A production by Th17-skewed skin resident cells which correlated with reduced human β defensin 2 expression in the skin. Our data suggests that inhibiting RORγt transcriptional activity by a low molecular weight inhibitor may hold utility for the treatment of Th17/IL-17-mediated skin pathologies.